A Mid-Holocene reindeer antler from Regstrup, Sjælland, Denmark - Bennike, Ole; Jensen, Theis Zetner Trolle; Taurozzi, Alberto John; Mackie, Meaghan; Claudi-Hansen, Lone; Magnussen, Betina (Danish Journal of Archaeology, 2022)
A small, shed antler fragment of a reindeer from Sjælland, Denmark has been dated to the Mid-Holocene, ca., 4700 cal B.C. Reindeer was an important component of the Lateglacial fauna in Denmark, and the species survived for ca. 1400 years into the Holocene. However, we consider it highly unlikely that this species inhabited Denmark during the Mid-Holocene, when dense forests characterized the vegetation and summer temperatures were somewhat higher than at present. We suggest that the reindeer antler came to Sjælland from Norway or Sweden as a result of trade, perhaps involving flint.